2018
DOI: 10.1590/1807-3107bor-2018.vol32.0030
|View full text |Cite
|
Sign up to set email alerts
|

Duration of effectiveness of Botulinum toxin type A in excessive gingival display: a systematic review and meta-analysis

Abstract: Botulinum toxin type A is effective in reducing excessive gingival display caused by hyperfunctional upper lip elevator muscles; however, this effect is transient. This study aimed to determine the duration of the effectiveness of botulinum toxin type A on a gummy smile. A systematic search was conducted using Medline (PubMed), Scopus, and Web of Science electronic databases, from 1970 to March 2017 with no language restriction; the search included studies evaluating adult patients with excessive gingival disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
19

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 34 publications
1
41
1
19
Order By: Relevance
“…On the other hand, when the discrepancy involves a nondentoalveolar etiology other approaches are necessary. In these cases, treatment could consist of orthognathic surgery, 9 botulin toxin injections, 10 lip repositioning surgery, 2,11 or the combination of therapies.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when the discrepancy involves a nondentoalveolar etiology other approaches are necessary. In these cases, treatment could consist of orthognathic surgery, 9 botulin toxin injections, 10 lip repositioning surgery, 2,11 or the combination of therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Chagas et al 11 y Pedron et al 12 afirman que existen varios procedimientos que pueden ser realizados para la corrección de la sonrisa gingival como: gingivoplastía, intrusión de dientes por medio de aparato ortodóntico, cirugía ortognática y resección ósea, los cuales están disponibles para reducir la sonrisa gingival. No obstante, esos tratamientos son altamente complejos y costosos.…”
Section: Tratamiento Para La Sonrisa Gingivalunclassified
“…In addition, Comparison results showed that increasing the number of injection points per side did not seem to lead to an improved aesthetic outcome. 45 A system review found that the effect tended to be stable until at least 8 weeks of follow-up, and the gingival exposure might not return to baseline within 12 weeks of follow-up. 45 Short-term adverse events such as asymmetric smile and difficulty in smiling were present solely in the first weeks following initial treatment.…”
Section: Isotretinoin For Plane Wartsmentioning
confidence: 99%